Камера тепла и холода для изделий фотоэлектронной техники. - Dunaenko, A. Kh.; Fotiy, V. D.; Ashcheulov, A. A. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The paper describes a heat and cold chamber (HCC) designed for measuring photoelectric parameters (PEP) and conducting reliability tests of photoelectronic devices in the temperature range from –60 to +100 °C. The chamber’s design enables measurement of PEP of radiant energy receivers (RER) in the visible and near-infrared spectral ranges under normal or reduced atmospheric pressure. The chamber can be easily placed directly on the measuring setup, which is crucial for ensuring stable operation of RER.